Approaches to Understanding Hadiths on Wearing Garments Below the Ankles (A Study of Mukhtalif al-Hadith) - Zaenal Arifin; Rahmat Zubandi Thahir; Ahmad Fawaid (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
This study examines approaches to understanding hadiths concerning the practice of wearing garments below the ankles (isbāl) through the framework of mukhtalif al-hadith. The issue of isbāl has generated diverse scholarly interpretations due to the presence of seemingly divergent prophetic narrations, some of which convey unconditional prohibition while others explicitly link the prohibition to moral intentions such as arrogance and pride. This research employs a qualitative library-based methodology, analyzing primary hadith collections alongside classical and contemporary scholarly works to explore patterns of interpretation and methodological reasoning.The findings reveal that hadiths on isbāl can be classified into two main textual categories: unconditional prohibitions and intention-based condemnations. Divergent legal conclusions among scholars are shown to stem primarily from methodological orientations rather than from disagreements over hadith authenticity. Scholars adopting literal-textual approaches tend to uphold a general prohibition, whereas those employing contextual and reconciliatory methods emphasize harmonization (al-jam‘ wa al-tawfīq) by interpreting the narrations within their ethical and socio-historical contexts.This study further demonstrates that ethical orientation emerges as the central interpretive outcome of isbāl hadiths. The prophetic guidance consistently prioritizes moral values such as humility, social equality, and the avoidance of arrogance over rigid formal regulation of dress length. By integrating textual classification, methodological analysis, and ethical interpretation, this research contributes to contemporary hadith studies by offering a coherent framework for addressing cases of mukhtalif al-hadith and reinforcing the relevance of ethical coherence in responsible and contextual hadith interpretation.